Review of the Sphaeropthalma imperialis species-group (Hymenoptera: Mutillidae), with descriptions of females and taxonomic notes - Pitts, James P. (Zootaxa, 2006)
A study of Schuster’s Sphaeropthalma imperialis and S. edwardsii species-groups was completed. Sphaeropthalma megagnathos aurifera Schuster is a junior synonym of S. megagnathos Schuster and S. edwardsii flammifera Schuster is a junior synonym of S. edwardsii (Cresson). New sex associations make S. imperialiformis maracopae Schuster and S. imperialiformis imperialiformis (Viereck) junior synonyms of S. marpesia (Blake), and S. erato (Blake) a junior synonym of S. imperialis (Blake). The S. imperialis species-group is redefined to contain S. imperialis (Blake) and S. marpesia, which were previously placed in the S. imperialis group sensu Schuster (1958), and S. megagnathos and S. edwardsii, which were previously placed in S. edwardsii group sensu Schuster (1958). The female of S. edwardsii is described and the females of S. imperialis and S. marpesia are redescribed. Keys are presented for both sexes of this species-group.